Three-dimensional radiochromic and polymer gel dosimeters with Pluronic F-127 matrix – a review of current research. (August 2019) - Kozicki, M; Jaszczak, M; Kwiatos, K; Maras, P; Kadlubowski, S; Wach, R; Dudek, M
Abstract: A co-polymer of poly(ethylene oxide)- block -poly(propylene oxide)- block -poly(ethylene oxide) (Pluronic F-127, PEO-PPO-PEO) was proposed as a physical gel matrix, substituting gelatine for three-dimensional polymer gel dosimeters and as a matrix for the preparation of new radiochromic gel dosimeters. Two polymer gel dosimeters and seven radiochromic gel dosimeters were obtained with this new matrix. In this review we summarise the main advantages of using Pluronic F-127 for manufacturing radiation dosimeters and the best performing new Pluronic dosimeters.